Peran Literasi Keuangan Dan Financial Self-Efficacy Dalam Mempengaruhi Perilaku Kredit Berisiko Melalui Paylater - Garin Pratiwi Solihati; Ikhyandini Garindia Atristyanti (ProBank, 2025)
This analysis explores the influence of both objective and subjective financial literacy, in addition to financial self-efficacy, on hazardous credit behavior among millennial PayLater users residing in Indonesia. A total of 262 participants provided data through an online survey, which was subsequently analyzed employing Structural Equation Modeling (SEM). The empirical evidence suggests that individual perceptions of financial literacy reduce engagement in high-risk credit activities while simultaneously bolstering one's financial self-efficacy. The acquisition of objective financial literacy solely enhances one's financial self-efficacy without directly impacting behaviors associated with high-risk credit engagement. Furthermore, financial self-efficacy does not demonstrate a statistically meaningful impact on precarious credit practices is recognized, and it does not fulfill a mediating role in the association between financial literacy and precarious credit practices. These results underscore the critical role of subjective financial literacy in alleviating the risk associated with adverse credit behaviors.